الأهمية الاقتصادية لاستصلاح الأراضي في رفع كفاءة الإنتاج الزراعي في سورية - الأسد عمران; خدام علي (Latakia University Journal -Biological Sciences Series, 2014)
تعد عملية استصلاح الأراضي إحدى أهم أساليب التوسع الأفقي والعمودي في القطاع الزراعي، التي تعمل على زيادة فعالية الاستثمارات من جهة، وتسريع وتيرة نمو الإنتاج من جهة أخرى. وتشمل عمليات استصلاح الأراضي مجموعة كبيرة من الإجراءات الهامة التي تؤثر بشكل مباشر على استخدام الأراضي الزراعية، وفي مقدمتها بناء السدود وإقامة أنظمة وشبكات ري وصرف حديثة، وغسيل الأراضي المتملحه، وحماية التربة من الانجراف والحت، ووقف زحف الصحراء، وتسوية أراضي المنحدرات، وتنقيتها من الحجارة، وبناء المدرجات في المنحدرات، وحفر الآبار الارتوازية، وتحسين المراعي وزراعة الأحزمة الخضراء وما إلى ذلك. لقد تم اعتماد إستراتيجية زراعية متعددة الأهداف في سورية تشمل في المقام الأول زيادة المساحات المستصلحة، وكذلك تأمين مياه الري من خلال بناء العديد من السدود لتبلغ المساحة المروية في سورية نحو)1399) ألف هكتار عام 2011، أي ما نسبته 24.5% من الأراضي المزروعة، هذا إلى جانب إدخال تقنيات الري الحديث (التنقيط والرذاذ)، لتصل نسبة المساحة المروية في عام 2011 وفق هذا الأسلوب إلى نحو 22.4% من إجمالي المساحة المروية في سورية. وقد انعكست تلك الإجراءات إيجاباً على إنتاجية المحاصيل والخضار والأشجار المثمرة. حيث بلغت في المحاصيل الشتوية المروية ما يعادل من 5 - 10 أضعاف المحاصيل الشتوية المزروعة بعلاً، وفي المحاصيل الصيفية المروية نحو (4) أضعاف المحاصيل الصيفية البعلية. The process of soil restoration is one of the most important methods of vertical and horizontal expansion in the agricultural sector; it works to increase the effectiveness of investments on the one hand, and to accelerate mass production on the other hand. The processes of reclamating lands include a big number of important procedures that directly affect the utilization of agricultural lands. On top of these procedures come: constructing dams, building modern systems and nets for irrigation and sanitation, reclamating saline soil, protecting soil from drift and erosion, stopping encroachment of desert, settling land slopes, getting rid of stones, building terraces in slopes, drilling artesian wells, improving pastures, and cultivation green belts. The Syrian government developed a multiple-target-agricultural strategy including primarily increasing the reclaimed areas, using modern techniques for irrigation (drip and spray), as well as providing water for irrigation through the construction of several dams. This made the total irrigated area in the country about 1399 thousand hectares in 2011, i.e. about 24.5% of the cultivated land. The percentage of irrigated areas using this method is about 22.4% of the total irrigated area in the country. These actions positively affected the productivity of crops, vegetables and fruit trees, so that the winter irrigated crops reached 5–10 times the non–irrigated crops, and the summer irrigated crops reached 4 times the non–irrigated crops.